Socio-demographic Characteristics and Related Factors Affecting Children with Autism Spectrum Disorder (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by social deficits, communicative difficulties and repetitive behaviors, with evidence of cognitive dysfunction. Approximately 1% of the world’s population or 67 million are affected by autism. ASD is an emerging public health issue globally which is associated with a huge burden on the family, community and the nation.Objective: To determine the socio-demographic characteristics and related factors affecting children with ASD to help the government and relevant organizations to take necessary steps to reduce burden of the families.Materials and Methods: This cross-sectional study was carried out from July 2015 to June 2016 among 154 children with ASD. Data were collected by face-to-face interview with semi-structured questionnaire following systematic random sampling technique.Results: Majority (73.4%) of the children were male and mean (±SD) age was 6.66±2.97 years. Most (88.8%) of the children were from urban areas with average monthly family income Tk. 41785.71±23936.45. Majority of the fathers (45.5%) and mothers (31.8%) had 'masters level'of education. Maximum (68.2%) children were from nuclear family and a few (9.1%) parents had a history of consanguineous marriage. Most (96.8%) of the children were initially treated by specialist doctors whereas, the majority (74.0%) were diagnosed in government hospitals. Most (89.6%) of the children were treated withspeech therapy.Conclusion: Since ASD is a growing public health problem in Bangladesh, countrywide proper early diagnostic facilities, especially in peri-urban and rural areas, should be available to measure its actual burden in the country.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 56-61